PENGEMBANGAN MEDIA KOMIK DIGITAL BERBANTUAN FLIPBOOK MATA PELAJARAN PENDIDIKAN PANCASILA MATERI PENERAPAN NILAI-NILAI PANCASILA SISWA KELAS II SDN KLENANG LOR 1 KABUPATEN PROBOLINGGO - Faradella Rahmadhini; Didit Yulian Kasdriyanto; Shofia Hattarina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop Flipbook-assisted digital comic media for the Pancasila Education subject in elementary schools, validated by material and media experts, and assessed through student and teacher response questionnaires. The method used is Research & Development (ADDIE model), consisting of five stages: analysis of learning needs and problems, storyboard design, development of digital comic media using Flipbook, Implementation through trials with second-grade students at SDN Klenang Lor 1, Probolinggo Regency, Evaluation based on validator feedback. The needs analysis revealed that second-grade students struggle to understand abstract concepts and quickly become bored with conventional text- and lecture-based teaching methods. Therefore, there is a need for interactive learning media that suits student characteristics.The developed digital comic media was validated by material experts with an average score of 84.61% and by media experts with a score of 80.88%, both categorized as